Supplementary data images and models for "An Image Based 3D Modelling Framework for Li-S Batteries" - Xiaoyu Dai; Nive Kulkarni; James Robinson; Dan Brett; Paul Shearing; Rhodri Jervis (University College London, 2022)
This repository contains the supplementary information data, includes images and models which were used in the referenced paper "An Image Based 3D Modelling Framework for Li-S Batteries".
The images contain tiff files of the original grayscale image from X-ray computed tomography of a commercial Lithium-Sulfur battery cathode, grayscale and segmented images of the full sample, segmented images of the subvolume sample.
The models contain the executable mph files for 3D electrochemical modelling work for Lithium-Sulfur battery, with the different cathode structure extracted from the corresponding subvolumes. Those file could be executed in COMSOL Multiphysics 6.0.
Keywords: 90499 Chemical Engineering not elsewhere classified